Establishment of myelinating Schwann cells and barrier integrity between central and peripheral nervous systems depend on Sox10. - Fröb, Franziska; Kichko, Tetyana; Reeh, Peter; Wegner, Michael; et al. (Glia, 2012)
The transcription factor Sox10 is expressed throughout Schwann cell development and has already been shown to be essential for specification and for the identity and further development of immature Schwann cells. Here, we show that Sox10 is also required in Schwann cells for establishing the myelinating state. This is concluded from the fact that a peripheral neuropathy develops in mice in which Sox10 is deleted by a Cre recombinase whose expression is under control of Krox20 regulatory elements. This neuropathy is characterized by altered marker gene expression along the peripheral nerve, decreased conductivity, and severe persistent hypomyelination. As the Cre recombinase is additionally active in boundary cap cells, we also analyzed the role of Sox10 during embryogenesis in establishment and maintenance of the boundary between central and peripheral nervous systems. Sox10 deletion did not affect establishment or survival of boundary cap cells but appeared to compromise barrier function as cells expressing oligodendrocyte and astrocyte markers were no longer restricted to the central nervous system, and instead found in peripheral nerves. We infer that in addition to its many roles in Schwann cells, Sox10 is also important for the integrity of the boundary between central and peripheral nervous systems. © 2012 Wiley Periodicals, Inc.
UnivIS-Import:2015-03-09:Pub.2012.med.IB.LPCIPDBI.establ
Keywords: Boundary cap cells; CMT; Glia; HMG; Krox20; Peripheral neuropathy; Sry; Transcriptional control